Novel heating- and deformation-induced phase transitions and mechanical properties for multicomponent Zr50M50, Zr50(M, Ag)50 and Zr50(M, Pd)50 (M = Fe, Co, Ni, Cu) amorphous alloys. (30th March 2022) - Ding, J.; Inoue, A.; Kong, F.L.; Zhu, S.L.; Pu, Y.L.; Shalaan, E.; Al-Ghamdi, A.A.; Greer, A.L.
Highlights: Zr50 M50 and Zr50 (M, NM)50 alloys show different heating-induced phase transitions. Zr50 M50 ribbons show plastic elongation under uniaxial tension and work-hardening. Deformation in tension induces B2, B33 phases and plate-like monoclinic precipitates. The B2 and B33 particles with high-density defects form by polymorphic transformation. Abstract: Multicomponent alloys of Zr50 M50, Zr50 (M, Ag)50 and Zr50 (M, Pd)50 (M = Fe, Co, Ni, Cu) can be melt-spun to obtain amorphous ribbons. The maximum thickness for fully amorphous ribbons varies with composition in the range 34‒53 μm. In contrast, fully amorphous ribbons are not obtainable for binary Zr50 Ni50 or ternary Zr50 (Ni, Cu)50 alloys. Heating-induced crystallization occurs through: two stages of amorphous [am] →[ am ′  + B2] → [B2 + B33] for Zr50 M50 ; and [am] → [ am ′  + B2] → [B2 + AgZr] for Zr50 (M, Ag)50 ; and a single stage of [am] → [B2] for Zr50 (M, Pd)50, while no B2 phase is formed for the binary and ternary Zr50 Q50 (Q = Ni or/and Cu) alloys. As-spun amorphous ribbons have good bending plasticity. Remarkably, Zr50 M50 ribbons in tension show 0.22‒0.28% plastic elongation and work-hardening (the yield stress is ∼820 MPa, the fracture stress is ∼1200 MPa). When cold-rolled at room temperature to 30% reduction in thickness, Zr50 M50 ribbons show 10% increase in hardness, while retaining good bending plasticity. Cold-rolling induces precipitation of spheroidal B2 and irregular B33 particles, while deformation in tension induces B2, B33 and also plate-like monoclinic precipitates. The B2 and B33 particles form by polymorphic transformation, and include a high density of internal defects. This novel deformation-induced precipitation has not been recognized for any Zr50 Q50 binary or ternary alloys. The new multicomponent systems are encouraging for future progress as structural amorphous alloys. Graphical abstract: Image, graphical abstract